2017
DOI: 10.3389/fmicb.2017.02547
|View full text |Cite
|
Sign up to set email alerts
|

Diverse CO2-Induced Responses in Physiology and Gene Expression among Eukaryotic Phytoplankton

Abstract: With rising atmospheric CO2, phytoplankton face shifts in ocean chemistry including increased dissolved CO2 and acidification that will likely influence the relative competitive fitness of different phytoplankton taxa. Here we compared the physiological and gene expression responses of six species of phytoplankton including a diatom, a raphidophyte, two haptophytes, and two dinoflagellates to ambient (~400 ppm) and elevated (~800 ppm) CO2. Dinoflagellates had significantly slower growth rates and higher, yet v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 76 publications
1
20
0
Order By: Relevance
“…This also suggests that the Chl a per cell must have on average been higher under this treatment, to account for the lack of an effect on total Chl a concentrations, although we have no direct data at the cellular level for this. Increases in Chl a per cell in response to high pCO 2 have been previously reported in multiple dinoflagellates (e.g., Eberlein et al, 2016;Hennon et al, 2017). However, Chl a per cell in diatoms has been reported to increase modestly (Crawfurd et al, 2011) to stay the same (e.g., Hennon et al, 2017) or decrease (Jacob et al, 2017) under high pCO 2 .…”
Section: Influence Of Elevated Pco 2 On Contrasting Phytoplankton Assmentioning
confidence: 83%
See 1 more Smart Citation
“…This also suggests that the Chl a per cell must have on average been higher under this treatment, to account for the lack of an effect on total Chl a concentrations, although we have no direct data at the cellular level for this. Increases in Chl a per cell in response to high pCO 2 have been previously reported in multiple dinoflagellates (e.g., Eberlein et al, 2016;Hennon et al, 2017). However, Chl a per cell in diatoms has been reported to increase modestly (Crawfurd et al, 2011) to stay the same (e.g., Hennon et al, 2017) or decrease (Jacob et al, 2017) under high pCO 2 .…”
Section: Influence Of Elevated Pco 2 On Contrasting Phytoplankton Assmentioning
confidence: 83%
“…Increases in Chl a per cell in response to high pCO 2 have been previously reported in multiple dinoflagellates (e.g., Eberlein et al, 2016;Hennon et al, 2017). However, Chl a per cell in diatoms has been reported to increase modestly (Crawfurd et al, 2011) to stay the same (e.g., Hennon et al, 2017) or decrease (Jacob et al, 2017) under high pCO 2 . Within the diatoms, the genera Skeletonema and Thalassiosira appeared to benefit more than others.…”
Section: Influence Of Elevated Pco 2 On Contrasting Phytoplankton Assmentioning
confidence: 83%
“…Lastly, cell size is generally correlated with genome size [77,78], and processes such as adaptive gene loss and genomic streamlining may optimize nutrient acquisition traits in small phytoplankton species, particularly in more stable environments [79]. Conversely, it is conceivable that larger cells may have a greater gene redundancy, leading to more resilient traits [8], which may provide a competitive advantage in dynamic environments. In summary, the higher flexibility of larger phytoplankton species in response to direct and indirect effects of warming and elevated pCO 2 may, at least partially, offset their competitive disadvantage in nutrient acquisition.…”
Section: …And the Large?mentioning
confidence: 99%
“…(CCMs) [5][6][7][8]. Various studies, however, have shown that elevated pCO 2 does not necessarily enhance primary production, or may even have negative effects, e.g.…”
mentioning
confidence: 99%
“…The anion exchange inhibitor DIDS does not inhibit the pH drift, whose extent probably relates to HCO 3 À entry, in the marine Glenodinium foliaceum (Nimer et al 1997). SLC4 HCO 3 À transporters are known from the genomes of a species of the (present) Symbiodiniaceae (Aranda et al 2016), Alexandrium monilatum and Prorocentrum minimum (Hennon et al 2017) and Thoracosphaera heimii (Van de Waal et al 2013e Waal et al 2013; presumably these are expressed in the plasmalemma. The various SLC4 HCO 3 À transporters can be Na + :HCO 3 À symporters or HCO 3 À :Clantiporters; work on the dinoflagellate SLC4 is needed to determine the co-or counter-ions, and their stoichiometry (Liu et al 2015, Raven 2020, Raven and Beardall 2020, and hence the possibility that this transporter brings about active HCO 3 À influx with corresponding accumulation of HCO 3 À in the cytosol.…”
Section: Mechanisms Of Active Transport Of Inorganic Cmentioning
confidence: 99%